The Music of Painting : music, modernism and the visual arts from Romantics to John Cage - Vergo, Peter (London : Phaidon Press, 2012)
Summmary /Publisher description. : "Composers and artists have always borrowed from each other. Peter Vergo, for the first time, offers an in-depth study of how and why, in the modernist era, music and painting became intertwined. Artist-composer relationships examined include Debussy's interest in Whistler, Tuner, and Monet, Franz Liszt's fascination with Raphael and Michelangelo, Kandinsky with Schoenberg and Paul Klee's influence from Polyphonic music. How artists attempted to translate musical rhythms, and structures into painting and how musicians developed visual themes, all within the backdrop to modernism, at a time of huge change in freedoms, industry, expression, ideological frameworks, and artistic practice."--
Nazivi poglavlja : Towards the condition of music -- 1. Wagnerian painting -- 2. Correspondences -- 3. Art-work of the future -- 4. Unknown regions -- 5. Art of fugue -- 6. Music and movement -- 7. Art, jazz and silence.
Bibliografija - Kazala
Keywords: metodika nastave povijesti umjetnosti -- muzika, motivi -- vizualna umjetnost -- glazba -- modernizam